The effect of several parameters on catalytic denitrification of water by the use of H2 in the presence of O2 over metal supported catalysts - Theologidis, Christodoulos; Savva, Petros G.; Olympiou, Georgios; Pantelidou, Nantia; Constantinou, B. K.; Chatziiona, Vasiliki; Valanidou, Lilian; Piskopianou, Charoula; Christophi, Costas A. (My University, 2013)
The present paper involves a detailed study of the selective catalytic reduction of nitrates in aqueous mediums by the use of H2 in the presence of O2 over monometallic and bimetallic supported catalysts. In this study, an attempt has been made to improve the denitrification efficiency (XNO3-, SN2) of several catalysts by regulating some experimental parameters that are involved in the process. Therefore, the effects of the type of reactor (semi-batch reactor vs continuous flow reactor), the nature of the active phase (Pd, Cu, and Pd-Cu) and the particle size of γ-Al2O3 spheres (particle diameter= 1.8 mm and 3 mm) on catalytic activity and reaction selectivity, as well as the adsorption capacity of γ-Al2O3 spheres for nitrates, were examined. As the review indicates, most of the research has so far been conducted on batch or semi-batch reactors. This study successfully demonstrates the benefits of using a continuous flow reactor in terms of catalytic activity (XNO3-, %) and reaction selectivity (SN2, %). Another important aspect of this study is the crucial role of bimetallic Pd-Cu clusters for the prevention of NH4+ formation. Moreover, the use of 1.8 mm diameter γ-Al2O3 spheres as a support was proved to significantly enhance the catalytic performance of bimetallic Pd-Cu catalysts towards nitrate reduction compared to 3 mm diameter γ-Al 2O3 spheres. This difference may be attributed to mass (NO3-, OH-) transfer effects (external mass transfer phenomena).
Keywords: Active species; Catalytic denitrification; DRIFTS; Mechanistic studies; SSITKA